Comparative Evaluation of Cinnamon Plant for Their Antimicrobial Efficacy against Pathogenic Bacteria - Verma, Khushbu; Chandra, Gulab; Singh, Ajay Pratap (Asian Journal of Pharmaceutical Research and Development, 2021)
Cinnamon was grounded in mortal and pestle with addition of 10ml distill water. Then it is subjected to vortex and centrifuged to collect the supernatent. This extract was collected in a test tube. In the qualitative phytochemical testing presence of various secondary metabolites were found viz. saponin, tannin, flavonoid, carbohydrate, protein, steroids, terpenoids and soluble starch. saponin, terpenoids and carbohydrate were found in abundance while protein, steroid, soluble starch, tanin and flavonoid were found in moderate amount. Less or no amount of alkaloids, phytosterols and phenol were found. In the quantitative analysis titration of ascorbic acid and citric acid were performed and spectrophotometry of carbohydrates and phenols were performed. Ascorbic acid and carbohydrate was found in moderate amount while citric acid and phenols were found in fewer amounts. Then the antimicrobial activity of cinnamon were studied by the disk diffusion method.The antibacterial activity of cinnamon against S. aureus and S. epidermis was found to be nil. Whereas the antifungal activity of cinnamon against A. niger was found quite good while no activity in A. candidus. The inhibitory effect of cinnamon is quite poor against p. corylophilum and Penicillium species.